The Two NF-κB Pathways Regulating Bacterial and WSSV Infection of Shrimp - Li, Chaozheng; Wang, Sheng; He, Jianguo (Frontiers in Immunology, 2019)
The outbreak of diseases ordinarily results from the disruption of the balance and harmony between hosts and pathogens. Devoid of adaptive immunity, shrimp rely largely on the innate immune system to protect themselves from pathogenic infection. Two nuclear factor-κB (NF-κB) pathways, the Toll and immune deficiency (IMD) pathways, are generally regarded as the major regulators of the immune response in shrimp, which have been extensively studied over the years. Bacterial infection can be recognized by Toll and IMD pathways, which activate two NF-κB transcription factors, Dorsal and Relish, respectively, to eventually lead to boosting the expression of various antimicrobial peptides (AMPs). In response to white-spot-syndrome-virus (WSSV) infection, these two pathways appear to be subverted and hijacked to favor viral survival. In this review, we will discuss the recent progress in elucidating microbial recognition, signal transduction, and effector regulation within both shrimp Toll and IMD pathways. Similarities and differences relative to their Drosophila or mammalian counterparts will also be discussed and highlighted. Understanding the interplay between pathogens and shrimp NF-κB pathways may provide new opportunities for disease-prevention strategies in the future.